You can achieve more live by design, not by default - Khera, Shiv (Bloomsbury Business, 2018)
If You Want To Stand Out Then You Need To Do Something Outstanding A person with a positive attitude cannot be stopped and a person with a negative attitude cannot be helped. Both success and failure have a limited lifespan. Success is neither a miracle nor a mystery. It does not depend upon special skills, formal education or superior intelligence. It is the natural outcome of consistently applying certain principles on an ongoing basis. The ultimate goal is to sustain success and eliminate failure. Acquiring facts is knowledge, understanding facts is comprehension, and the proper application of facts is wisdom. The principles in this book can help you to: 1. Live by design, not by default 2. Gain confidence and optimize your potential 3. Become proactive and develop a winning attitude 4. Balance your health, wealth and relationships 5. Overcome day-to-day problems and make better decisions 6. Make positive choices and avoid pitfalls The secret to a meaningful life is in your hands. Through inspiring ideas and basic values, this book will help empower you to Achieve More and become unstoppable.